2010
DOI: 10.1002/dmrr.1130
|View full text |Cite
|
Sign up to set email alerts
|

The glycolipid sulfatide protects insulin‐producing cells against cytokine‐induced apoptosis, a possible role in diabetes

Abstract: In the present study, we report the ability of sulfatide to significantly reduce apoptosis, cellular leakage and NO production in insulin-producing cells. Data suggest this is not due to induction of β-cell rest. Our findings indicate a possible implication for sulfatide in the pathogenesis of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…For example, administration of C16:0-sulfatide, specifically, to Zucker fatty rats, which express a defective leptin receptor, reduced fasting insulin and improved the first-phase insulin response and glucose-stimulated insulin response (Blomqvist et al 2005). More generally, sulfatide was shown to protect isolated islet cells from apoptosis, iNOS expression, and nitric oxide secretion induced by cytokines; this protective effect was not specific to C16:0-sulfatide (Roeske-Nielsen et al 2010). These findings indicate that sulfatide exerts a protective effect in pancreatic islets via normalization of insulin secretion and protection from inflammation.…”
Section: Sphingolipids In the Diabetic Pancreasmentioning
confidence: 99%
“…For example, administration of C16:0-sulfatide, specifically, to Zucker fatty rats, which express a defective leptin receptor, reduced fasting insulin and improved the first-phase insulin response and glucose-stimulated insulin response (Blomqvist et al 2005). More generally, sulfatide was shown to protect isolated islet cells from apoptosis, iNOS expression, and nitric oxide secretion induced by cytokines; this protective effect was not specific to C16:0-sulfatide (Roeske-Nielsen et al 2010). These findings indicate that sulfatide exerts a protective effect in pancreatic islets via normalization of insulin secretion and protection from inflammation.…”
Section: Sphingolipids In the Diabetic Pancreasmentioning
confidence: 99%
“…Although proinflammatory cytokines have been implicated in apoptosis of nucleated cells (Roeske-Nielsen et al 2010), their pro-apoptotic effects were not observed when fresh or pRBCs were maintained in the presence of TNF and/or IL-1 (Pattanapanyasat et al 2010). Our results are also in accordance with the possible refractoriness of RBCs to cytokine-induced apoptosis (Neote et al 1994, Daniels 2007) because IFN-γ levels were elevated at stages of infection that were related (late stage) and not related (early stage) to nRBC apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is a key autoantigen in type 1 diabetes, giving rise to both anti-insulin autoantibodies and T cell autoreactivity in preclinical models and new-onset patients [38], [39]. Sulfatide protects insulin-producing cells from cytokine-induced apoptosis [40] and increased insulin production together with reduced sulfatide expression may be an unfortunate combination negatively affecting local immune homeostasis and, hence, may serve as an important checkpoint in the pathogenesis of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%